2013
DOI: 10.1371/journal.pone.0052206
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Tobacco-Related Health Warning Labels across Socioeconomic, Race and Ethnic Groups: Results from a Randomized Web-Based Experiment

Abstract: BackgroundThe U.S. Family Smoking Prevention and Tobacco Control Act of 2009 requires updating of the existing text-only health warning labels on tobacco packaging with nine new warning statements accompanied by pictorial images. Survey and experimental research in the U.S. and other countries supports the effectiveness of pictorial health warning labels compared with text-only warnings for informing smokers about the risks of smoking and encouraging cessation. Yet very little research has examined differences… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
120
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(130 citation statements)
references
References 59 publications
8
120
1
Order By: Relevance
“…Hispanic ethnicity, however, remained an important predictor of anticipated behavior among specific subgroups of young adult cigarette smokers. Cantrell et al (2013) found that graphic HWLs were similarly effective across racial/ethnic subgroups among an adult population of smokers. Our findings suggest that graphic labels may be more effective among 18-to 34-year-old Hispanic lighter, nondaily, and "social" smokers, suggesting there may be subgroups within the smoking population among whom graphic warning labels will have greater impact.…”
Section: Sourcementioning
confidence: 89%
See 1 more Smart Citation
“…Hispanic ethnicity, however, remained an important predictor of anticipated behavior among specific subgroups of young adult cigarette smokers. Cantrell et al (2013) found that graphic HWLs were similarly effective across racial/ethnic subgroups among an adult population of smokers. Our findings suggest that graphic labels may be more effective among 18-to 34-year-old Hispanic lighter, nondaily, and "social" smokers, suggesting there may be subgroups within the smoking population among whom graphic warning labels will have greater impact.…”
Section: Sourcementioning
confidence: 89%
“…Graphic HWLs also lead some viewers to forego cigarettes, a behavioral reaction that, along with cognitions about quitting, is one of the strongest predictors of subsequent quitting . A recent randomized controlled trial showed that the nine FDA graphic warning labels had a consistently greater impact than text-only labels on message salience, perceived impact, credibility, and intention to quit across diverse populations (Cantrell et al, 2013).…”
mentioning
confidence: 99%
“…Cantrell and colleagues 18 found no significant interaction between race/ethnicity or education and treatment condition (GWLs or TWLs) on salience, perceived impact, credibility, or quit intentions. In similar studies, Hammond and colleagues 19 found no significant condition-by-education interaction on overall perceived effectiveness of the warnings and Thrasher and colleagues 20 found no significant condition-by-race interactions on credibility, believability, or personal relevance of the warnings.…”
Section: Assessing the Consequences Of Implementing Graphic Warning Lmentioning
confidence: 95%
“…Other studies suggest that GWLs are as effective among disadvantaged groups as among the general population [18][19][20][21] and thus have a neutral effect on disparities. Cantrell and colleagues 18 found no significant interaction between race/ethnicity or education and treatment condition (GWLs or TWLs) on salience, perceived impact, credibility, or quit intentions.…”
Section: Assessing the Consequences Of Implementing Graphic Warning Lmentioning
confidence: 99%
“…In the same year University of South Carolina: terrifying images are more effective then informing pictures by a study done in Canada, Mexico, Brazil (Cantrell et al, 2013). A cross-sectional study in England in 2008 and in 2011, including 11-16 year-old, about 1400 people, where groups were: non-smokers, experimental and regular smokers.…”
Section: Eye-tracking Studiesmentioning
confidence: 99%